Higher-order human telomeric G-quadruplex DNA metalloenzyme catalyzed Diels–Alder reaction: an unexpected inversion of enantioselectivity modulated by K+ and NH4+ ions1. Issue 67 (28th August 2015) - Li, Yinghao; Wang, Changhao; Hao, Jingya; Cheng, Mingpan; Jia, Guoqing; Li, Can
<x xml:space="preserve">Abstract</x> K+ and NH4+, bearing approximately equal ionic radius, present different allosteric activation for higher-order human telomeric G-quadruplex DNA metalloenzyme.